La nature et l'intérêt du crédit-bail en informatique - Gilbert, Claude (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1988)
Third-party leasing is now part and parcel of new contractual forms that have appeared with the development of commerce. Moreover, progress in new technologies has given birth to computer contracts. In the same way that the originality of third-party leasing has stimulated thinking on the legal nature of this operation in Civil law, the technical complexity of considerations due under computer contracts has brought about the adoption of clauses specifically adapted to this type of covenant. Since the third-party lease is used to finance the acquisition of computer equipment, the ensuing note attempts to analyse the legal consequences of two converging enigmas. Briefly stated, third-party computer leasing is characterized by the distinction between hardware and software (of which the latter does not in principle lend itself to leasing operations), the particular importance of obligations on guarantees by the supplier with regard to the user, and to the presumption of technical ignorance on the part of the user. The second of these characteristics is normal in third-party leases and the last occurs frequently in computer contracts.